Remittances and educational attainment: Evidence from Tajikistan - Sebastian Köllner (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2013)
This paper examines the impact of remittances on educational attainment in Tajikistan using the Tajikistan Living Standards Measurement Survey (TLSS) from 2007 and 2009. Applying an ordered probit framework and controlling for hetereoskedasticity, censoring, intra-family correlation, and different masures of remittances, we find a negative impact of receiving remittances on educational outcomes. Calculations of the marginal effects draw a more subtle picture indicating that remittances positively affect educational achievements as long as education is mandatory. For higher, non-mandatory levels of education, however, receiving remittances negatively influences educational attainment. These results support concerns regarding the wide-spread affirmative impact of remittances on human capital formation. Accounting for endogeneity, the coefficients of the remittance variables become insignificant. Our general findings, however, remain unchanged implying that remittances are not used for investments in human capital accumulation once education becomes voluntary.
Keywords: 330